2015
DOI: 10.3109/01443615.2015.1007343
|View full text |Cite
|
Sign up to set email alerts
|

Is lateral localisation of placenta a risk factor for adverse perinatal outcomes?

Abstract: The aim of this study was to evaluate the relationship between placental localisation and perinatal outcomes. This study was performed in a tertiary centre hospital by retrospectively analysing the medical records of patients who were followed up and underwent delivery in the same hospital. The patients were divided into two groups according to the placental locations (central and lateral) in their routine sonographic findings between the 18 and 24 weeks' gestation. Out of 1,057 patients, 87.4% (n = 919) had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 14 publications
4
24
2
3
Order By: Relevance
“…In some studies, posterior or central (anterior or posterior) placental location has been reported to be associated with a lower risk of complications than other placental locations, and consequently, posterior placental location was chosen as the reference category …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, posterior or central (anterior or posterior) placental location has been reported to be associated with a lower risk of complications than other placental locations, and consequently, posterior placental location was chosen as the reference category …”
Section: Methodsmentioning
confidence: 99%
“…As the anatomical conditions vary across different areas of the uterus, both with respect to the shape of the cavity and the blood supply, other placental locations than previa may also be associated with adverse pregnancy, delivery and infant outcomes. Several previous studies have indicated this, but study groups have been relatively small and results are partly contradictory …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Seckin et al prospective study also showed the relationship between lateral placenta and development of preeclampsia (4.5% versus 1.6% in lateral and central placenta respectively) and fetal growth restriction. 7 Gonser et al study (n=148) also showed odd ratio 3.1 in lateral (n=115) versus central (n=33) group for development of preeclampsia. 8 Fung et al also studied prospectively the location of placenta and pregnancy outcome and found the odds ratio of 2.04 for preeclampsia and 1.82 for small for gestational age (SGA) in lateral group.…”
Section: Discussionmentioning
confidence: 84%
“…Non-central placental location in the second trimester was associated with an increase risk of adverse obstetric outcomes including preeclampsia [OR = 2.27; 95 % confidence intervals (CIs), 1.31-3.93]. Secken et al [7] also found preeclampsia significantly higher in the lateral placental location group (4.5 vs. 1.6 %; p = 0.027).…”
Section: Discussionmentioning
confidence: 98%